Empathy and Altruism as a Mediator in the Relationship between Mindfulness and Social Behavior for the Sultan Qaboos University Students during COVID-19 - Hassan, Abdulhameed S. (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The present study aimed to build a theoretical model proposed for the causal relationship between the four variables of the study, and then validate the proposed model by examining the direct and indirect effect of Mindfulness to Social Behavior, and whether Empathy and Altruism mediate the relationship between Mindfulness and Social Behavior. The sample of the study consisted of 270 college students (144 females,126 male), to achieve the study goals researcher used three validated scales (Johnson, Burke, Brinkman& Wade, 2016; Steele et al. 2008; Allison, Baron-Cohen & Wheelwright, 2011). The results of path analysis showed that Empathy and Altruism are a mediator variable between the relationship of national Mindfulness and Social Behavior, this mediation was partial.